HEARJACK - The Ultimate Posture Enhancement and Skin Health Jacket for Military Excellence - Mardamsyah, Adam; Ferry Fadri, Muhammad; Fazil Rais, M; Firmansyah, Arief; Reychan Perdana, Alvin (Pusat Publikasi Nusantara, 2024)
HEARJACK is an innovative smart jacket designed to enhance the health and well-being of military personnel. This groundbreaking project addresses the crucial need for maintaining proper posture, monitoring heart health, and managing humidity-related skin issues. Spinal alignment and posture play a fundamental role in overall well-being, and deviations from a healthy alignment can lead to various health issues. HEARJACK integrates sensors like the MPU6050 for real-time posture monitoring, DHT11 for humidity insights, and a heart rate sensor for stress assessment. These sensors, combined with an IoT algorithm, enable continuous monitoring and data analysis. The results demonstrate a significant improvement in posture, reduced skin-related health concerns, and enhanced stress management, underscoring the potential of IoT-driven wearables in military healthcare. Further research and development promise to revolutionize health and military technology